Evaluating the effectiveness of transferrin receptor‐1 (TfR1) as a magnetic resonance reporter gene. (29th February 2016) - Pereira, Sofia M.; Herrmann, Anne; Moss, Diana; Poptani, Harish; Williams, Steve R.; Murray, Patricia; Taylor, Arthur
Abstract : Magnetic resonance (MR) reporter genes have the potential for tracking the biodistribution and fate of cells in vivo, thus allowing the safety, efficacy and mechanisms of action of cell‐based therapies to be comprehensively assessed. In this study, we evaluate the effectiveness of the iron importer transferrin receptor‐1 ( TfR1 ) as an MR reporter gene in the model cell line CHO‐K1. Overexpression of the TfR1 transgene led to a reduction in the levels of endogenous TfR1 mRNA, but to a 60‐fold increase in total TfR1 protein levels. Although the mRNA levels of ferritin heavy chain‐1 ( Fth1 ) did not change, Fth1 protein levels increased 13‐fold. The concentration of intracellular iron increased significantly, even when cells were cultured in medium that was not supplemented with iron and the amount of iron in the extracellular environment was thus at physiological levels. However, we found that, by supplementing the cell culture medium with ferric citrate, a comparable degree of iron uptake and MR contrast could be achieved in control cells that did not express the TfR1 transgene. Sufficient MR contrast to enable the cells to be detected in vivo following their administration into the midbrain of chick embryos was obtained irrespective of the reporter gene. We conclude that TfR1 is not an effective reporter and that, to track the biodistribution of cells with MR imaging in the short term, it is sufficient to simply culture cells in the presence of ferric citrate. Copyright © 2016 The Authors Contrast Media & Molecular Imaging Published by John Wiley & Sons Ltd. Abstract : We evaluate transferrin receptor‐1 ( TfR1 ) as an MR reporter gene in the model cell line CHO‐K1. Although under standard culture conditions iron levels increase significantly on overexpression of this gene, we found that medium supplementation with iron sources results in dramatically higher levels of intracellular iron and MR contrast, irrespective of the reporter. We conclude that TfR1 is not an effective reporter, and that for short‐term cell tracking it is sufficient to simply supplement culture medium with ferric citrate.